A public health crisis: how to address structural racism in health policy writing. Week 7: Making big problems, smaller - OER project materials - Rowh, Marta, author (Colorado State University. Libraries, 2022)
Health Policy is a complex and rigorous field that brings together health research, health systems, and social determinants of health. Numerous professional organizations, including the American Medical Association (AMA) and American Public Health Association (APHA), have identified structural racism as a public health crisis and students are eager to gain the tools needed to address these issues. Effective policies require an understanding of structural racism as well as issues of equity versus equality in healthcare. Students are keen to gain skills in developing and writing health policy, but often find addressing the overarching realities of structural racism within policy to be daunting and overwhelming. This 10-session course presents an introduction to analyzing basic research, understanding structural racism and a framework for writing public health policy, presented in a stepwise fashion, developing a firm foundation on each concept individually and then creatively demonstrating a connection between the individual parts.
A public health crisis Week 7: Making big problems, smaller - OER project materials
This 10-week course of materials were collected for the OER project funded by the Colorado OER Council Grant (AY 2021).
Keywords: systemic racism; structural racism; health policy writing; public health policy